2009
DOI: 10.1007/s10886-009-9645-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ligands of Porcine Olfactory Binding Proteins

Abstract: Knowledge of endogenous ligands of olfactory binding proteins is a prerequisite for studying their role in odor and pheromone transduction. Here, we report the extraction, derivatization, and characterization by gas chromatography-mass spectrometry of the natural ligands of pig, Sus scrofa (L.), Von Ebner's Gland protein (VEG) and odorant binding protein (OBP). We identified two isoforms (VEG1 and VEG2), which differed only by the linkage of an O-N-acetylglucosamine (O-GlcNac) group on VEG1. The natural ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Recombinant OBPs from P. pastoris, isoforms or total protein, did not bind testosterone. This result was expected from the in-gel binding assay with native OBP that did not bind testosterone (Le Danvic et al 2009), which is the natural ligand of VEG (Von Ebner's Gland protein), another protein of the nasal mucus. Whatever the ligand, OBP-Pichia-iso2 displayed the same behavior as total OBP-Pichia; that could be explained by the fact that it is the closest to total OBPPichia, in terms of phosphorylation.…”
Section: Ligand Binding Monitored By Fluorescence Spectroscopymentioning
confidence: 57%
See 2 more Smart Citations
“…Recombinant OBPs from P. pastoris, isoforms or total protein, did not bind testosterone. This result was expected from the in-gel binding assay with native OBP that did not bind testosterone (Le Danvic et al 2009), which is the natural ligand of VEG (Von Ebner's Gland protein), another protein of the nasal mucus. Whatever the ligand, OBP-Pichia-iso2 displayed the same behavior as total OBP-Pichia; that could be explained by the fact that it is the closest to total OBPPichia, in terms of phosphorylation.…”
Section: Ligand Binding Monitored By Fluorescence Spectroscopymentioning
confidence: 57%
“…In addition, we demonstrated recently that a dynamic mechanism involving PTM could be responsible for OBP diversity and specificity (Le Danvic et al 2009;Nagnan-Le Meillour et al 2009b). Indeed, porcine OBP can be posttranslationally modified by phosphorylation, and we suggested that this PTM could generate a diversity of OBP isoforms with specific binding properties (Nagnan-Le Meillour et al 2009b).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Solution-based affinity binding is commonly characterized using methods such as UV-absorption [8], differential and titration calorimetry [9], matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) [10] and electrophoretic separation [11]. Surface-based affinity binding, which is widely used in affinity biosensors [12], can be investigated with methods such as protein arrays [13], immunoassays [14], and thermal-shift assays [15], which use fluorescent or radioactive labeling groups to signal binding events.…”
Section: Introductionmentioning
confidence: 99%
“…The calyx is a barrel structure composed of eight β‐sheets in alternating reverse orientation, with α‐helix linkages between some of the individual sheets (Grzyb et al, 2006). The binding of lipocalins to specific ligands plays a role in many biological functions, including olfaction (Lazer et al, 2002; Le Danvic et al, 2009), coloration (Cianci et al, 2002; Wade et al, 2009), immune response (Logdberg and Wester, 2000; Clifton et al, 2009), pheromone transport (Miyawaki et al, '95; Magert et al, '99; Chamero et al, 2007), prostaglandin synthesis (Nagata et al, '91; Fouchecourt et al, 2002) and allergen response (Virtanen et al, '99; Virtanen, 2001). Retinol binding protein (RBP), which is found in human, rat and other species, is the canonical member of the lipocalin family.…”
mentioning
confidence: 99%